Smart public transportation at your fingertips - Rojas, Juan Pablo; Bustos, Julio César; Ordóñez Camacho, Diego (Enfoque UTE, 2017)
QBus is a system that locates the bus routes circulating in the city of Quito. It consists of a mobile application which uses either Bluetooth Low Energy technology or Quick Response codes to identify the stops. It is based on the location of the user to show the nearest stops and search the available bus routes. The application shows relevant information of each route and, using a digital map, draws its path and the stops it performs. In addition to this, it offers the "How do I get there" functionality that allows the user to search the available bus routes to move from one point to another within the city. In order to comply with this process, QBus performs a search of the bus routes that have stops near the points of origin and destination; this functionality indicates to the user the stop in which he must take the bus and in which it must get off. On the other hand the system consists of a web portal which allows to manage all the information of the application, ie cooperatives, stops and bus routes in a graphical way through the use of the Google Maps V3 API.